HUKUM DAN ETIKA DAKWAH - Izmuddin, Iiz (IAIN Bukittinggi, 2009)
A missionary endeavor is a God’s command. There are two kinds of law related with the missionary endeavor called as fardlu ‘ain and fardlu kifayah. The meaning of fardlu ‘ain is an obligation for every Moslem, while fardlu kifayah is an obligation to all every Moslem; the others Moslem should not do the obligation when one Moslem have done it. It considered as fardlu ‘ain if we observe a Moslem as a single personality. Every Moslem has an obligation to have a missionary endeavor in his or her life. Then, it considered as fardlu kifayah when a Moslem of a society has done the obligation instructed. Indirectly, all Moslem in the society should not do the same thing in the same way the Moslem. To carry out the obligation of a missionary endeavor, there are some important things that must to be pay attention such as wisdom ways, there are full of tenderness, sympatric, a wisdom words indicates good advices and etc.